Important role of stratospheric injection height for the distribution and radiative forcing of smoke aerosol from the 2019-2020 Australian wildfires - Heinold, Bernd; Baars, Holger; Barja Gonzalez, Boris; Christensen, Matthew; Kubin, Anne; Ohneiser, Kevin; Schepanski, Kerstin; Schutgens, Nick; Senf, Fabian; Schroedner, Roland; Villanueva, Diego; Tegen, Ina (My University, 2022)
More than 1 Tg smoke aerosol was emitted into the atmosphere by the exceptional 2019-2020 southeastern Australian wildfires. Triggered by the extreme fire heat, several deep pyroconvective events carried the smoke directly into the stratosphere. Once there, smoke aerosol remained airborne considerably longer than in lower atmospheric layers. The thick plumes traveled eastward, thereby being distributed across the high and mid-latitudes in the Southern Hemisphere, enhancing the atmospheric opacity. Due to the increased atmospheric lifetime of the smoke plume, its radiative effect increased compared to smoke that remains in lower altitudes. Global models describing aerosol-climate impacts lack adequate descriptions of the emission height of aerosols from intense wildfires. Here, we demonstrate, by a combination of aerosol-climate modeling and lidar observations, the importance of the representation of those high-altitude fire smoke layers for estimating the atmospheric energy budget. Through observation-based input into the simulations, the Australian wildfire emissions by pyroconvection are explicitly prescribed to the lower stratosphere in different scenarios. Based on our simulations, the 2019-2020 Australian fires caused a significant top-of-atmosphere (TOA) hemispheric instantaneous direct radiative forcing signal that reached a magnitude comparable to the radiative forcing induced by anthropogenic absorbing aerosol. Up to +0.50Wm(-2) instantaneous direct radiative forcing was modeled at TOA, averaged for the Southern Hemisphere (+0.25Wm (-2) globally) from January to March 2020 under all-sky conditions. At the surface, on the other hand, an instantaneous solar radiative forcing of up to 0.81Wm(-2) was found for clear-sky conditions, with the respective estimates depending on the model configuration and subject to the model uncertainties in the smoke optical properties. Since extreme wildfires are expected to occur more frequently in the rapidly changing climate, our findings suggest that high-altitude wildfire plumes must be adequately considered in climate projections in order to obtain reasonable estimates of atmospheric energy budget changes.
Keywords: Forcing (mathematics); Atmospheric models